Burden, access, and disparities in kidney disease - Deidra C. Crews; Aminu K. Bello; Gamal Saadi (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2019)
Kidney disease is a global public health problem that affects more than 750 million persons worldwide.1 The burden of kidney disease varies substantially across the world, as does its detection and treatment. Although the magnitude and impact of kidney disease is better defined in developed countries, emerging evidence suggests that developing countries have a similar or even greater kidney disease burden. In many settings, rates of kidney disease and the provision of its care are defined by socioeconomic, cultural, and political factors, leading to significant disparities in disease burden, even in developed countries.3 These disparities exist across the spectrum of kidney disease-from preventive efforts to curb development of acute kidney injury (AKI) or chronic kidney disease (CKD), to screening for kidney disease among persons at high risk, to access to subspecialty care and treatment of kidney failure with renal replacement therapy (RRT). World Kidney Day 2019 offers an opportunity to raise awareness of kidney disease and highlight disparities in its burden and current state of global capacity for prevention and management. In this editorial, we highlight these disparities and emphasize the role of public policies and organizational structures in addressing them. We outline opportunities to improve our understanding of disparities in kidney disease, the best ways for them to be addressed, and how to streamline efforts toward achieving kidney health equity across the globe.